Novel alloxazine analogues: design, synthesis, and antitumour efficacy enhanced by kinase screening, molecular docking, and ADME studies - Doaa Samaha; Sawsan Mahmoud; Mosaad Sayed Mohamed; Rokaia S. Abdullah; Nageh A. Abou Taleb; Tomohisa Nagamatsu; Hamed I. Ali (Journal of Enzyme Inhibition and Medicinal Chemistry)
This study describes the development of novel alloxazine analogues as potent antitumor agents with enhanced selectivity for tumour cells. Twenty-nine out of 45 newly compounds were investigated in vitro for their growth inhibitory activities, against two human tumour cell lines, namely, the human T-cell acute lymphoblastoid leukaemia cell line (CCRF-HSB-2) and human oral epidermoid carcinoma cell line (KB), and the antitumor agent “Ara-C” was used as a positive reference in this investigation. Compounds 9e and 10J were the highest among their analogues, against both tumour cell lines (CCRF-HSB-2 and KB). Correlation analyses demonstrated a strong relationship between the IC50 values and AutoDock binding free energy or calculated inhibition (Ki). The study delves into structure–activity relationships (SARs) through advanced modelling tools integrated with structure-based drug design (SBDD) using GOLD 5.2.2, AutoDock 4.2, and Accelrys Discovery Studio 3.5. Physicochemical properties, pharmacokinetics, drug-likeness, and toxicity predictions of the most potent alloxazine derivatives were conducted using ProTox-II and Swiss ADME for effective antitumor agents with improved selectivity.